GIS-based multi-criteria land suitability assessment for potential agroforestry area expansion in Uttarakhand - Mishra, Deepak Kumar; Kumar, Ujjwal; Arunachalam, Kusum (Indian Journal of Agroforestry, 2023)
In the western Indian Himalayan region, deforestation or forest degradation due to human activities, soil erosion due to intensive farming, and fallow land due to migration, it becomes necessary to make conservation efforts. The present study aims to assess the suitability of the land that has the potential to be used for agroforestry expansion. Land use mapping was done using supervised image classification on Landsat 8 OLI satellite data. The result showed that the agroforestry area was abundant at the altitude <600 m asl followed by 1100-1600 m asl and 600-1100 m asl. Maximum agroforestry was found in slope <10˚, followed by 20˚-30˚ and 30˚-40˚ slope. In the Dehradun district, areas under fallow land, degraded forest area, and wasteland are 108.405 km2, 82.04 km2, and 176.3 km2, respectively. For land suitability analysis weighted overlay method was used with altitude, slope and available land as criteria. The land suitability analysis result showed that the 93.44 km2 area is highly suitable for expanding agroforestry, followed by 144.75 km2 area as moderately category and 53.79 km2 as least suitable. The geographical distribution of land suitable for expansion aids in identifying opportunities for increasing tree cover under agroforestry systems and leveraging the benefits of ecosystem services.